Boron-incorporated IrO2-Ta2O5 coating as an efficient electrocatalyst for acidic oxygen evolution reaction - Huang, Quanbo; Zhuang, Shaojie; Zheng, Yuexi; Peng, Xinyuan; Ye, Zhiguo; Li, Duosheng (Chemical engineering journal (Lausanne, Switzerland : 1996), 2024)
[Display omitted] •The incorporation of boron species dramatically boosts the intrinsic activity of high-stabilized IrO2-Ta2O5.•The incorporation of boron species modulates the energy barrier of Ir sites for acidic OER.•A nearly complete rutile-type crystal structure ensures ultrahigh durability of the electrocatalysts. The Ir-based electrocatalysts for the acidic oxygen evolution reaction (OER) have demonstrated remarkable durability. Enhancing the Ir-based electrocatalytic activity still remains crucial owing to the scarcity of iridium. Here, a high-temperature sintering technique is employed to fabricate a boron (B)-incorporated IrO2-Ta2O5 coating with an almost perfect rutile-type crystal structure on a corrosion-resistant titanium substrate, ensuring exceptional stability for the acidic OER. The B-incorporated IrO2-Ta2O5 electrode fabricated in a mixed solution of 0.6 M H3BO3, exhibits an overpotential of 210 mV at a current density of 10 mA cm−2 and a lower Tafel slope of 34.2 mV dec−1 in a 0.5 M H2SO4 solution, which is far lower than the 272 mV overpotential and the 45.3 mV dec−1 of the IrO2-Ta2O5/Ti electrode. The electrode possesses a minimal potential increase even after undergoing continuous OER for 400 h at a high current density of 100 mA cm−2 in a 0.5 M H2SO4 solution. The incorporation of B species into IrO2-Ta2O5 effectively fine-tunes the electronic structure of Ir active sites, leading to a substantial enhancement of the intrinsic electrocatalytic activity. This study provides promising prospects for reducing the energy consumption of noble IrO2-based electrocatalysts in the practical application of electrochemical industry for the acidic OER.